1976
DOI: 10.1113/jphysiol.1976.sp011299
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of the transmission of labelled protein by the proximal and distal regions of the small intestine of young rats.

Abstract: SUMMARY1. The plasma volume in rats aged 15-16 days was measured by dilution analysis using homologous, 1251-labelled immunoglobulin G. A mean plasma volume of 5-53 ml./100 g and a mean blood volume of 8-01 ml./100 g were obtained.2. After the injection of labelled immunoglobulin G into the heart, homogenates of various abdominal organs and of the carcass were prepared. Labelled immunoglobulin G left the vascular compartment at a rate of about 9-10 %/hr over a 3 hr period. About 11 % of the labelled immunoglob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 18 publications
4
43
0
Order By: Relevance
“…Labelled rat IgG leaves the vascular compartment at about 9-10 %/hr (Morris & Morris, 1976). The input of intact rat IgG by the enterocytes, after the injection of 1 mg of labelled rat IgG into the proximal small intestine, greatly exceeds this removal rate.…”
Section: B Morris R Morris and R Solari Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Labelled rat IgG leaves the vascular compartment at about 9-10 %/hr (Morris & Morris, 1976). The input of intact rat IgG by the enterocytes, after the injection of 1 mg of labelled rat IgG into the proximal small intestine, greatly exceeds this removal rate.…”
Section: B Morris R Morris and R Solari Discussionmentioning
confidence: 99%
“…We have suggested, based on our previous studies (Morris & Morris, 1976& Morris, , 1977, that there may be two pathways for homologous IgG transport through proximal enterocytes: one route involving receptors and affording complete protection to the molecule and another route with no protection, leading to the release of small molecular weight fragments into the circulation. The experiments reported in this paper were designed to compare the uptake and transmission of homologous and heterologous immunoglobulins and other protein molecules by proximal enterocytes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmission of intact immunoglobulin G (JgG) to the circulation of young rats, occurs in the proximal region of the small intestine. The distal region (ileum) does not transmit intact IgG (for references see Morris & Morris, 1976). It has been suggested that the passage of intact IgG through the proximal enterocytes involves attachment to receptors and that such attachment affords protection to the IgG molecules and is pH-dependent.…”
Section: P Physiological Society December 1977mentioning
confidence: 99%
“…Walker et al (89) showed that in rats the absorption of antibodies was the same in jejunum and ileum. However, Morris and Morris (56) found that the proximal small intestine of rats is the site of antibody permeation. A specific mechanism of uptake and transport of maternal immunoglobulins has been demonstrated only in rats (72,92).…”
Section: Introductionmentioning
confidence: 99%